ANALISA TEKNIS PENGGANTIAN MAIN ENGINE PADA KAPAL GENERAL CARGO “KM. GEMILANG” 1054 GT - Mustafidurijal Mustafidurijal; Kiryanto Kiryanto; Untung Budiarto (Jurnal Teknik Perkapalan, 2013)
Main engine replacement done on the ship KM. Gemilang due to technical problems. This was done because the shipyard trouble getting spare parts for the machine used an old production machinery and funds available is only enough to buy a main engine with lower power. The purpose of the preparation of this study was to determine the effect of replacing the main engine of the speed and foundation construction machinery KM. Gemilang and analyze alternative propeller used as a solution to obtain propeller designs that have high propulsion efficiency, and the optimum ratio of gear box according to a new machine. The methodology used in this study include field studies, literature study and analysis. Field studies conducted by collecting engineering drawings and interviews to parties in PT. Jasa Marina Indah Shipyard Semarang. Literature studies conducted both in the form of various reference books, journals on-line, etc. Analysis of the calculation is done by making modeling ship engine foundations, calculating ship resistance and thrust at each speed, calculate the appropriate analysis propeller specifications and provide analysis of alternative recommendation from the calculation. From these calculation, it was decided to use the power of main engine with a 1100 hp with engine data: MAN manufacturing, model: D284LE410, Type 4 stroke air, 2200 rpm, bore: 128mm, 142 mm stroke, compression ratio of 15:1, SFOC 210 lt/ h, gearbox models R6-250, dimensions 1791 x 1230 x 1105 (mm), and weighs machine 2160 kg. The result of the analysis of propeller that has the highest efficiency on the Matching Point condition is Propeller Type : B4.40, Diameter : 1200 mm, Pitch : 960 mm, Pitch Diameter ratio : 0,80, Expanded Area Ratio: 0.40